Analysis of Tourism Development Strategies Through Community Based Tourism Models at Maria Village Cultural Tourism - Trisna, Trisna; Kaluge, David; Satria, Dias (AIBPM Publisher, 2024)
The variables used in this research are community participation, job creation, relationships between communities, environmental and cultural preservation and cultural tourism in Maria Village. The aim of this research is to determine the influence of community participation, job creation, relationships between communities, environmental and cultural preservation on Maria Village cultural tourism. The population in this study was the Maria Village community, while the sample used was the community who participated in the development of Maria Village tourism. The sampling technique in this research is a simple random sampling technique. The data collection method used (instrument) used was a questionnaire. This research uses quantitative research methods. The results of this research are that community participation (X1) has an effect on Maria Village tourism (Y), job creation (X2) has an effect on Maria Village tourism (Y), relations between communities (X3) has an effect on Maria Village tour (Y). Cultural and environmental sustainability (X4) influences Maria Village tourism (Y).